Clinicophysiological, haematobiochemical and electrocardiographic effects of homogenous and heterogenous blood transfusion in traumatized dogs - SINGH, AMITA; JADON, N S (The Indian Journal of Animal Sciences, 2019)
Twenty four clinical cases of dogs having the history of the accidents irrespective of their age and sex were included in this study. The definite diagnosis was made on the basis of haematobiochemical, radiographic, ultrasonographic and laparoscopic findings. The animals were divided randomly into 3 groups, viz. A, B and C comprising equal number of animals. After the definite diagnosis, patients were subjected to surgical intervention i.e. splenectomy. The animals of groups A, B, and C were subjected to the administration of anaesthetic combination of atropine sulphate, diazepam and thiopental sodium just to pass endotracheal tube followed by either isoflurane (2–2.5%) or sevoflurane (3–3.5%) and also subjected to whole blood transfusion of cattle, buffalo and dogs in groups A, B & C respectively either during the operation or just after the operation.The efficacy of blood transfusion was judged on the basis of effects on various clinicophysiological and haematobiochemical parameters recorded before and after the administration of blood. Electrocardiographic studies were also made. It was concluded that in case of the trauma of spleen, homogenous transfusion of the blood in traumatized patient is most beneficial however in case of the emergency condition, heterogenous blood transfusion from cattle and buffaloes may also be made to save the life of the patients.